Performance Assessment Team’s Performance in Filling The Position of The Sub-District Head in Buru Selatan District Maluku Province (Jurnal MSDA (Manajemen Sumber Daya Aparatur), 2023)
This research aimed to investigate the performance of the Civil Servants’ Performance Assessment Team in the appointment of sub-district head position in South Buru Regency. This research also identified both supporting and hindering factors as well as the efforts made to overcome existing obstacles. This qualitative descriptive research was performed using an inductive approach. Both primary and secondary data sources were utilized in this research. The data analysis techniques included data selection, classification, and verification. The data sources encompassed physical locations, individuals, and written materials. Data collection methods comprised interviews, observations, and documentation. The observations revealed that the performance of the Civil Servants’ Performance Assessment Team in filling the sub-district head position in South Buru Regency deviated from applicable regulations, as it failed to adhere to objective assessment during the implementation process. The efforts made to address this issue involved participation in education and training programs, adherence to primary responsibilities and functions, and budget requests to the South Buru Regency government to enhance the deficient facilities and infrastructure supporting the team's performance. To improve the process of selecting sub-district heads and minimize external influences, the author recommended policy reformulation that incorporated the principles of a merit system, thus promoting objectivity.ABSTRAK Penelitian ini bertujuan untuk mengetahui bagaimana kinerja Tim Penilai Kinerja PNS dalam pengisian jabatan camat di Kabupaten Buru Selatan, disamping itu juga untuk mengetahui faktor pendukung dan penghambat serta upaya yang dilakukan dalam mengatasi kendala yang ada. Metode penelitian yang digunakan adalah metode penelitian deskriptif kualitatif dengan pendekatan induktif. Sumber data pada penelitian ini adalah sumber data primer dan sekunder. Teknik analisis data yang digunakan adalah menyeleksi data, klasifikasi data dan verifikasi data. Sumber data yang digunakan place, person dan paper. Teknik pengumpulan data meliputi wawancara, observasi dan dokumentasi. Hasil pengamatan menggambarkan bahwa kinerja Tim Penilai Kinerja PNS dalam pengisian jabatan camat di Kabupaten Buru Selatan belum sesuai dengan peraturan yang berlaku karena dalam proses pelaksanaanya mengabaikan penilaian secara objektif. Upaya yang telah dilakukan adalah dengan mengikuti pelaksanaan pendidikan dan latihan, bekerja sesuai dengan tupoksi, mengajukan anggaran kepada pemerintah Kabupaten Buru Selatan untuk dapat melengkapi sarana dan prasarana yang masih kurang dalam menunjang kinerja Tim Penilai Kinerja PNS. Adapun saran dari penulis menegenai pengisian jabatan camat adalah merumuskan kembali kebijakan-kebijakan dengan memperhatikan prinsip-prinsip merit system sehingga dapat meminimalisir intervensi dan pengaruh luar yang menyebabkan proses pemilihan jabatan camat menjadi tidak objektif.